Redescription of the western Balkan species Xerocampylaea waldemari and its phylogenetic relationships to other Urticicolini (Gastropoda: Hygromiidae). Issue 4 (19th May 2019) - Proćków, Małgorzata; Duda, Michael; Kruckenhauser, Luise; Maassen, Wim J. M.; de Winter, Anton J.; Mackiewicz, Paweł
Abstract : The proper identification of species has significant implications for conservation and general knowledge of ecosystem variety. It is especially important for biodiversity hotspots and former Pleistocene refugia, such as the Balkans. In this paper, we evaluate the taxonomic status of the endemic Balkan species Fruticicola waldemari A. J. Wagner, 1912, using both recently collected material and museum specimens. Phylogenetic analyses based on two mitochondrial markers, 16S rRNA and cytochrome c oxidase subunit I, show that this species is closely related to the representatives of Xerocampylaea, including a conchologically similar and partly sympatric species, X. erjaveci . Analyses of shell and genital morphology as well as mitochondrial DNA sequences indicate that X. waldemari and X. erjaveci are separate but closely related species. These species differ in shell morphology (size, umbilicus diameter, microsculpture) as well as genital morphology. Nevertheless, a further study with more comprehensive sampling of both taxa is required to fully understand the complex pattern of genetic and morphological variation observed.